BRAND CHOICE AND REFERENCE GROUP: A QUANTITATIVE APPROACH OF BABY SKIN CARE PRODUCTS IN MANADO - Saerang, Gracia S; Massie, James D.D.; Gunawan, Emilia M (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: There are many baby skin care products available in the market that came by same purposes but in different brand name. From the existing brands, there are perfectly good in each of the products. The discussion group that has been formed is usually called as a Reference Group, which is about a person or group of people that provide information or suggestion for parents? brand choice. The objective of this research is to measure the influence of reference group through parents brand choice. This research used quantitative analysis. The population in this research refers to the consumers in Manado and samples used in this study of 100 respondents. The results showed Informational Influence, Utilitarian Influence, and Value-expressive Influence have a significant effect on consumer brand choice simultaneously. Informational influence has significant effect on consumer brand choice partially. Utilitarian influence does not have a significant effect on consumer brand choice partially. Value-expressive influence has significant effect on consumer brand choice partially. The marketers in the marketing field should increase the products popularity by improving the features of a product each brand, and the quality that ensure the babies are safe using the certain product. Keywords: brand, consumer brand choice, reference group.